2013
DOI: 10.1371/journal.pone.0054429
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Social Meaning of Infertility and Childbearing: A Qualitative Study of the Perception of Childbearing and Childlessness in Northern Ghana

Abstract: BackgroundInfertility is a major medical condition that affects many married couples in sub-Saharan African and as such associated with several social meanings. This study therefore explored community's perception of childbearing and childlessness in Northern Ghana using the Upper West Region as a case study.MethodsThe study was exploratory and qualitative using in-depth and key informant interviews and focus group discussions. Fifteen marriage unions with infertility (childless), forty-five couples with child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 18 publications
7
108
1
3
Order By: Relevance
“…The social reaction towards a woman as the sole cause of a couples' infertility is distressing and may affect her self-esteem (26,27). Men and women both experience the effects of infertility but compared to women; men uncommonly express concern about its impact on the stability of their marriage (11).…”
Section: Resultsmentioning
confidence: 99%
“…The social reaction towards a woman as the sole cause of a couples' infertility is distressing and may affect her self-esteem (26,27). Men and women both experience the effects of infertility but compared to women; men uncommonly express concern about its impact on the stability of their marriage (11).…”
Section: Resultsmentioning
confidence: 99%
“…The child-bearing abilities of young people across cultures are often valued by parents and grandparents. 17 This suggests that acknowledging family values and expectations in sexual health education may be effective for promoting safe sexual behaviours among young people.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of infertility among Ghanaian women have found an association with high rates of distress and depression (Alhassan, Ziblim, & Muntaka, 2014;Donkor & Sandall, 2007;Tabong & Adongo, 2013b). Takyi and Broughton (2006) found that ethnic identification may influence divorce.…”
Section: Family and Fertility In Ghanamentioning
confidence: 95%
“…Infertility can be devastating, especially for women, upon whom the blame for infertility disproportionately falls (Fledderjohann, 2012;Hollos et al, 2009;Tabong & Adongo, 2013b).…”
Section: Family and Fertility In Ghanamentioning
confidence: 99%
See 1 more Smart Citation